Tarekat dan Perkembangan Dakwah di Indonesia - Aripudin, Acep (Jurnal Ilmu Dakwah, 2011)
Since born until here development, sufism institution or tarekat canât be unthoucable from Islam. More than, tarekat is medium in preaching and difution of Islamic velue with their problem in the fact. The role of tarekat in Islmic difution to Indonesia has been noticed history very clearness. According to Martin van Bruinessen in his book Kitab Kuning sad that the demonstration of sufis with charismatic and it power was interested local community to converse to religion trader from Gujarat. More than, the local kings has feel same with the other and finally, the king olso followed to new religion sufis.